Transcriptome analysis of Gossypium reveals the molecular mechanisms of Ca2+ signaling pathway on arsenic tolerance induced by arbuscular mycorrhizal fungi - Gong, Minggui; Bai, Na; Su, Jiajie; Wang, Yuan; Wei, Yanan; Zhang, Qiaoming (Frontiers in Microbiology, 2024)
Introduction Arbuscular mycorrhizal fungi (AMF) have been demonstrated their ability to enhance the arsenic (As) tolerance of host plants, and making the utilization of mycorrhizal plants a promising and practical approach for remediating As-contaminated soils. However, comprehensive transcriptome analysis to reveal the molecular mechanism of As tolerance in the symbiotic process between AMF and host plants is still limited. Methods In this study, transcriptomic analysis of Gossypium seedlings was conducted with four treatments: non-inoculated Gossypium under non-As stress (CK0), non-inoculated Gossypium under As stress (CK100), F. mosseae-inoculated Gossypium under non-As stress (FM0), and F. mosseae-inoculated Gossypium under As stress (FM100). Results Our results showed that inoculation with F. mosseae led to a reduction in net fluxes of Ca2+, while increasing Ca2+ contents in the roots and leaves of Gossypium under the same As level in soil. Notably, 199 and 3129 differentially expressed genes (DEGs) were specially regulated by F. mosseae inoculation under As stress and non-As stress, respectively. Through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation and enrichment analyses, we found that under As stress, F. mosseae inoculation up-regulated a significant number of genes related to the Ca2+ signaling pathway genes, involved in cellular process, membrane part, and signal transduction. This suggests a potential role in mitigating As tolerance in Gossypium seedlings. Furthermore, our analysis identified specific DEGs in transcription factor families, including ERF, MYB, NAC, and WRKY, that were upregulated by F. mosseae inoculation. Conversely, MYB and HB-other were down-regulated. The ERF and MYB families exhibited the highest number of up- and down-regulated DEGs, respectively, which were speculated to play an important role in alleviating the As toxicity of Gossypium. Discussion Our findings provided valuable insights into the molecular theoretical basis of the Ca2+ signaling pathway in improving As tolerance of mycorrhizal plants in the future.